The Relationship between Serum Endocan Levels and Depression in Alzheimer's Disease. (26th January 2016) - Yoon, Kyung Hee; Kim, So Yeon; Moon, Yoo Sun; Roh, Daeyoung; Lee, Sang Kyu; Kim, Do Hoon
Abstract : Objectives . Growing evidence suggests that angiogenic vascular factors may be involved in the pathogenic mechanism of Alzheimer's disease (AD), and recently endocan has been proposed as an angiogenic biomarker. The aim of this study was to measure serum endocan levels according to the presence of depression in AD and to investigate the association among the serum endocan levels, cognitive function, and depression in these patients. Methods . Serum endocan levels were measured in 26 AD patients with depression, 29 AD patients without depression, and 29 healthy controls using an enzyme-linked immunosorbent assay kit. The Mini-Mental State Examination-Korean version (MMSE-KC) and the Korean version of the Geriatric Depression Scale-Short Form (SGDS-K) were used to evaluate cognitive function and depressive symptoms, respectively. Results . Serum endocan levels were significantly lower in AD patients with depression than in AD patients without depression or healthy controls. Serum endocan levels were negatively correlated with SGDS-K scores but not with MMSE-KC scores in AD patients. Conclusions . This study suggests that serum endocan levels might be associated with depression in AD. Future studies are needed to investigate the pathophysiological mechanisms or the role of endocan in AD with depression.